O trabalho de assistentes sociais na Política de Educação Básica em Diadema - SP: desafios durante e pós-pandemia do Coronavírus (COVID-19) - Santos, Douglas Alves dos (2024)
Social work in education has been a field of activity for social workers since the genesis of the profession in Brazil. In the field of education, this insertion finds a space of professional possibilities and challenges. We participate in the training processes of the working class, both in the institutional dimension (guaranteeing access and permanence) and in the political dimension in the struggle for public, secular and quality education. Over the last few decades, Social Work's role in national education policy has expanded, and there has been more reflection on the importance of education and professional work in the occupational spaces that make up this social policy. The subject of this doctoral thesis is the result of concern about the great neglect with which the National Education Policy has historically been treated and which has been aggravated during the difficult period of the coronavirus pandemic. The lack of organization and effective measures to guarantee access to the content of online classes has damaged the teaching-learning process and will have lasting impacts on the school environment, especially with the greater suffering of the subaltern classes of the Brazilian population. The general objective of the research is to understand the impacts of the covid-19 pandemic on the Basic Education Policy and on the work of Social Workers and the Social Center team of the Diadema - SP Secretariat, during the period between 2020-2022 and the challenges in the post-pandemic. The thesis was based on bibliographical research in books, magazines, websites and documents on the subject of Social Work in Education. Considering the relevance of systematizing professional experience, we sought to highlight the contribution of this form of qualitative research. A questionnaire was drawn up with triggering questions about the actions carried out by the Social Services team during the pandemic. Reflecting on the possibilities for social workers to work with the school community during the pandemic made it possible to find out how professionals adapted and built strategies to guarantee the right to access to education in the municipality. Professional work in Education Policy involves the struggle for the materialization and consolidation of social rights, as a mediation for the construction of another sociability, and this requires effort and a construction that is collective